Stilizacija vsakdanjega življenja - Ule, Mirjana (Družboslovne razprave, 1998)
The stylisation of life is a complex term which comprises different forms (themes) of individuals everyday life and suits the increasing need for the reflexive forms of everyday life in contemporary market societies. Growing necessity of thematisation and reflection of everyday life mirrors also in the interest the social sciences increasingly show for the everyday life of individuals and groups. Market and media mediated lifestyles present an issue or rather terminate the three major achivements of the modern industrial era: the class stratification of society, the national state and the division of social spheres (especially the division into the private and public sphere as well as the division into working time and free time). Lifestyle is the society, during which the individual "gathers" various "capital shares" which are significant for the environment and through which the person can become meaningful. Contemporary individualised lifestyles are mundane, transnational, althought not also anational. The paper draws attention to the ambivalent nature of the stylisation of everyday life, namely the division between the possibility of afirmative, emancipatory form of individual and stylistic usage, and the hidden but effective constraints for individuals.
Keywords: vsakdanje življenje; social psychology; socialna psihologija; individualizacija; identiteta